1991
DOI: 10.1007/bf01973497
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of halogenated industrial chemicals with transthyretin and effects on thyroid hormone levels in vivo

Abstract: Previous results in experimental systems have suggested that hydroxylated PCBs may decrease thyroid hormone levels through associative interaction with transthyretin. In the present paper it was investigated whether this property was also shared by various industrial chemicals, mainly pesticides. In total, 65 compounds from 12 chemical groups were analyzed for direct interference with the T4 binding site of transthyretin using a competitive binding assay. Sixty per cent of the compounds were competitive at a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…In young adult rats, RA is displaced from its serum transport protein, retinol binding protein, and the transthyretin-retinol binding protein complex by PCB 77 (112). Similar effects by PCB 77 on binding to transport proteins and serum levels of T 4 have been reported (99,105). Subchronic exposure to 2 , 2´, 3 , 3´, 4 , 4´-h e x a c h l o r o b i p h e n y l decreased kidney and liver levels of vitamin A and significantly lowered frontal cortex dopamine levels in rats dosed for 4 weeks after weaning (113).…”
Section: Xenobiotic Interference With the Thyroid Systemsupporting
confidence: 52%
See 1 more Smart Citation
“…In young adult rats, RA is displaced from its serum transport protein, retinol binding protein, and the transthyretin-retinol binding protein complex by PCB 77 (112). Similar effects by PCB 77 on binding to transport proteins and serum levels of T 4 have been reported (99,105). Subchronic exposure to 2 , 2´, 3 , 3´, 4 , 4´-h e x a c h l o r o b i p h e n y l decreased kidney and liver levels of vitamin A and significantly lowered frontal cortex dopamine levels in rats dosed for 4 weeks after weaning (113).…”
Section: Xenobiotic Interference With the Thyroid Systemsupporting
confidence: 52%
“…Chemical exposure can also lead to a decrease in serum protein-bound iodide levels, perhaps largely due to inhibition of the thyroid peroxidase enzyme, which disrupts the normal production of thyroid hormone (96)(97)(98). The displacement of T 4 /T 3 from the transport proteins (TBG, transthyretin, and albumin) may result in decreased ability of thyroid hormone to reach its target tissue and may facilitate the transport of the chemicals into the fetus (92,99). Chemical disruption of the T 4 /T 3 metabolism can influence deiodinase, glucuronidase, and sulfatase activity, and may ultimately result in increased biliary elimination of T 4 /T 3 .…”
Section: Xenobiotic Interference With the Thyroid Systemmentioning
confidence: 99%
“…thyroid binding globulin, transthyretin and albumin) may result in decreased ability of THs to reach its target tissue and then, may facilitate the transport of the chemicals into the fetus (Brouwer et al, 1998;Van den Berg et al, 1991). Boas M et al European Journal of Endocrinology 2006;154:599-611).…”
Section: Chemical Interferences With the Thyroid Systemmentioning
confidence: 99%
“…Inhibition of deiodinase enzymes can result as decrease in T3 available to elicit thyroid action at tissue level (Maiti & Kar, 1997). Conversely, deiodinase activity may increase in response to TD exposure, either as direct effect or in response to increased clearance of T4/T3 by the chemical stimulation of glucuronidase or sulfatase enzymes (Spear et al, 1990;van Raaij et al, 1993). Brucker-Davis (Brucker-Davis, 1998) suggested that such increases in the metabolism and in the clearance of T3 could result in goiter as the thyroid gland increases production to maintain proper TH levels.…”
Section: Chemical Interferences With the Thyroid Systemmentioning
confidence: 99%
“…Pesticides like chlorophenols, chlorophenoxy acids, organochlorines, and quinones have been shown to alter thyroid gland function and to reduce circulating thyroid hormone levels (60,61). A reduction of thyroid hormone levels can compromise the catalytic activity of hepatic cytochrome P450 monooxygenases and result in an altered hepatic androgen metabolism (62).…”
Section: Endocrine-disrupting Chemical Effectsmentioning
confidence: 99%